Creative conflict in african american thought : frederick douglass, alexander crummell, booker t. washington, w. - Moses, Wilson Jeremiah, 1942- (Cambridge Univ Press, 2004)
Professor Moses has here revised and brought together essays that focus on the complexity of, and contradictions in, the thought of five major African-American intellectuals: Frederick Douglass, Alexander Crummell, Booker T. Washington, W.E.B. DuBois, and Marcus M. Garvey, questioning both popular and scholarly conceptions of them as villains or heroes.